Nurses' and midwives' perspectives on participation in national policy development, review and reforms in Ghana: a qualitative study - Angela Kwartemaa Acheampong; Lillian Akorfa Ohene; Isabella Naana Akyaa Asante; Josephine Kyei; Gladys Dzansi; Charles Ampong Adjei; Samuel Adjorlolo; Francis Boateng; Philomena Woolley; Felix Nyante; Lydia Aziato (BMC, 2021)
Abstract Background The World Health Organization has admonished member countries to strive towards achieving universal health coverage (UHC) through actionable health policies and strategies. Nurses and midwives have instrumental roles in achieving UHC via health policy development and implementation. However, there is a paucity of empirical data on nurses and midwives' participation in policy development in Ghana. The current study explored nurses and midwives' participation in policy development, reviews and reforms in Ghana. Methods A qualitative descriptive exploratory design was adopted for this study. One-on-one individual interviews were conducted after 30 participants were purposefully selected. Data was audiotaped with permission, transcribed and analyzed inductively using the content analysis procedures. Results Two main themes emerged from the data: participation in policy development and perspectives on policy reviews and reforms. The findings showed that during health policy development and reviews, nurses in Ghana were overlooked and unacknowledged. Policy reforms regarding bridging the pre-service preparation gap, staff development and motivation mechanisms and influence on admission into nursing schools were raised. Conclusion The authors concluded that nurses and midwives are crucial members of the healthcare systems and their inputs in policy development and reviews would improve health delivery in Ghana.